Evaluating the Development Level of Agriculture Rating Rural Settlements for Wilderness Tourism Development Using ELECTERE III Techniques: A Case Study in Khurbiabanak - Mohammad Salmani; Seiedali Badri; Mohammadgavad Ghassabi; Ghadir Ashournejad (جغرافیا و پایداری محیط)
Despite the fact that a large amount of academic research in Iran have been allocated to tourism studies in recent years, yet it must be acknowledged that the development of tourism, especially in rural areas has not been paid enough attention and planning. In this regard, it appears to be essential to present a hierarchical classification of tourism areas and establish an effective framework for distributing tourists, delivering appropriate services, and desired function. Rural settlements of Khurbiabanak city with its unique features for the development of tourism can play an effective role in the further development of this region. This study investigates the potentials and capabilities of the rural settlements. While introducing unique features and capabilities of this area, this study tried to give priority to the rural settlements of areas in the light of their capabilities and levels of tourism development in order to attract tourists and allocate more infrastructure services. This applied study relying on deep field studies, using quantitative models, has resulted in a ranking of rural settlements in the mentioned area. To reach these goals, at the beginning of the study, using experts’ advises and previous studies in this field, the researchers set their criteria and indicators. Then, after completing the paired comparison questionnaires by expert and applying the hierarchical process (AHP), the weight of each criterion has been determined. After that, conducting (ELECTERE) technique, rating villages accomplished. In this study, the Expert Choice software was employed for the Analytical Hierarchy Process (AHP). The results indicated that villages such as Byazeh, Jandagh, Mehrjan, Garmeh, and Ayraj were given higher priority in tourism ranking in the abovementioned area.